Flash Pyrolysis Experiment on Albizia odoratissima Biomass under Different Operating Conditions: A Comparative Study on Bio-Oil, Biochar, and Noncondensable Gas Products. (9th July 2022) - Sowmya Dhanalakshmi, C.; Kaliappan, S.; Mohammed Ali, H.; Sekar, S.; Depoures, Melvin Victor; Patil, Pravin P.; Subbaiah, Baskara Sethupathy; Socrates, S.; Birhanu, Habtewolde Ababu
Abstract : This study deals with the flash pyrolysis of Albizia odoratissima biomass wastes at different temperature, sweep gas flow rate, and heating rate in a fluidized bed reactor. In the first phase of the experimental work, the effect of temperature (350–550°C) on product yield was analyzed, the second and third phases of the work were to analyze the effect of sweeping gas (N2 ), flow rate (1.25–2.25 m 3 /hr), and heating rate (20–40°C/min). The experimental works were carried out to get maximum bio-oil production. The experimental results demonstrated that the maximum yield of bio-oil was obtained at a temperature of 450°C, N2 flow rate of 1.75 m 3 /hr, and heating rate of 30°C/min. Temperature was found to be the crucial factor rather than sweep gas flow rate in the product distribution. Fourier transform infrared spectroscopy (FT-IR), gas chromatography mass spectroscopy (GC-MS), and elemental analysis were done on the obtained bio-oil, biochar, and noncondensable gas products. The heating value of the bio-oil and biochar was identified as 18.15 and 23.47 MJ/kg, respectively. The chemical analysis of the bio-oil showed that the oil is a mixture of phenol and oxygenated elements. The gas analyses showed that hydrogen and carbon dioxide were dominant, followed by carbon monoxide and methane.